SYNTHESIS, CHARACTERIZATION, DFT MODELING AND IN VITRO ANTIMYCOBACTERIAL ACTIVITY ASSAYS OF A SILVER(I)-ISONIAZID COMPLEX - Paris Junior, Jose Alberto; Cavicchioli, Mauricio [UNESP]; Amaral Machado, Rachel Temperani [UNESP]; Pavan, Fernando [UNESP]; Nakahata, Douglas Hideki; Corbi, Pedro Paulo; Ferreira Costa, Adao Marcos; Pereira, Douglas Henrique; Massabni, Antonio Carlos (Soc Brasileira Quimica, 2021)
In the present work, a silver(I) complex with the antimycobacterial drug isoniazid (inh) is described. Elemental and thermogravimetric analyses confirmed a 1:1 metal:ligand ratio for the silver-isoniazid (Ag-inh) complex with molecular composition AgC6H7N3O center dot NO3. Infrared (IR) analysis suggests a bidentate coordination of isoniazid to silver by the nitrogen of the NH2 group and by the oxygen of the C=O group, and also confirms the presence of free nitrate anion. Coordination by the NH2 group was reinforced by NMR measurements. Computational simulations using the density functional theory (DFT) reinforced that the ligand coordinates to the silver atom by the NH2 and C=O groups. The silver complex presented a minimal inhibitory concentration (MIC90) of 0.78 mu g/mL against the standard Mycobacterium tuberculosis strain H37Rv. The data reported herein warrants further investigation on Ag-inh complex as a potential agent against tuberculosis.
Keywords: metallodrugs; bioinorganic chemistry; molecular modeling; Mycobacterium tuberculosis; antibacterial assays